2006
DOI: 10.1300/j013v43n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promoting Behaviors Through Pregnancy, Maternity Leave, and Return to Work: Effects of Role Spillover and Other Correlates

Abstract: Women's health-promoting behavior changes and their correlates across the transition to motherhood and return to work are insufficiently understood. The purpose of this study was to describe and compare women's health-promoting behaviors, particularly physical activity (PA), across these transitions. A prospective, observational design was employed to assess 243 female healthcare workers from 3 sites with regard to health-promoting behaviors, and their demographic (e.g., age, parity) and psychosocial (i.e., wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Unfortunately, in our analysis, we were unable to differentiate between leisure-time activity and household activity. Other research has shown that with entry to parenthood, leisure-time activity is replaced by household activity because of a change in roles (Candelaria et al 2012;Grace et al 2006;Scharff et al 1999;Sternfeld et al 1999). As mothers usually engage more often in the care of children, their physical activity related to child-care (e.g., spending time on the playground or carrying the child) may be an important influence lacking in fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in our analysis, we were unable to differentiate between leisure-time activity and household activity. Other research has shown that with entry to parenthood, leisure-time activity is replaced by household activity because of a change in roles (Candelaria et al 2012;Grace et al 2006;Scharff et al 1999;Sternfeld et al 1999). As mothers usually engage more often in the care of children, their physical activity related to child-care (e.g., spending time on the playground or carrying the child) may be an important influence lacking in fathers.…”
Section: Discussionmentioning
confidence: 99%
“…In a smaller Canadian study, there was little change in PA during pregnancy, maternity leave, and on return to work, and PA remained below recommended levels 1 year post-partum [17]. In contrast, in the study of Swedish teenagers, having children increased the risk of inactivity in women but not in men [15].…”
Section: Introductionmentioning
confidence: 86%
“…Our review yielded eight independent datasets that fit these criteria [36,40,45,52,66,78,79,107]. All used self-reported PA as a dependent variable with the exception of Rhodes et al [45] who assessed MVPA with accelerometry.…”
Section: Parenthoodmentioning
confidence: 99%
“…All used self-reported PA as a dependent variable with the exception of Rhodes et al [45] who assessed MVPA with accelerometry. Six studies examined women exclusively [36,40,45,52,79,107], three studies had exclusive assessments of men [45,52,79], and two studies contained an amalgam of men and women under ''parents'' [66,78]. Among women, five of the six studies [36,40,45,52,79] showed a significant and small to medium sized effect decline in PA related to motherhood.…”
Section: Parenthoodmentioning
confidence: 99%